A Study on Annotations Under the Theory of Paratext in Translation - Pan, Li-na (Cultural and religious studies, 2022)
This paper mainly studies the basic types of annotation and the analysis of its effective functional usage, so as to pay more attention to annotation in the translation of poetry and Fu. The annotation of this study belongs to the category of paratext. Annotation is attributed to the paratext, undertakes its special function, enriches and perfects the paratext system.